Crosstalk of JNK1-STAT3 is critical for RAW264.7 cell survival - Wu, Qinghua; Wang, Xu; Wan, Dan; Li, Juan; Yuan, Zonghui (Cellular signalling, 2014)
T-2 toxin, a major compound of trichothecenes, inhibits protein synthesis and induces inflammation and cell apoptosis through the activation of MAPK pathway. The JAK/STAT pathway has recently been shown to be downstream targets of trichothecenes. However, whether there is any crosstalk between JNK and JAK/STAT pathways in trichothecene toxicity has not been studied. In the present study, we explored this potential in RAW264.7 cells treated with T-2 toxin. Our results revealed a crosstalk between JNK1 and STAT3 after T-2 toxin treatment, which was mediated by K-Ras. T-2 toxin treatment resulted in rapid phosphorylation, and more importantly, JNK1-STAT3 signaling pathway was shown to maintain the normal function of the mitochondria and to inhibit T-2 toxin-induced apoptosis. Therefore, this pathway was considered to be a potential cell survival pathway. Breakdown and degranulation of ribosomes in the rough endoplasmic reticulum and swelling of mitochondria were clearly visible after the cells had been incubated with T-2 toxin for 12h. Our data suggest that T-2 toxin had a Janus face: it induced both apoptotic and cell survival pathways. These results suggest that the crosstalk and the balance between MAPK and JAK/STAT pathway might be involved in T-2 toxin-induced apoptosis in RAW264.7 cells.
Keywords: Animals; Ribosomes; biologické modely; apoptóza; Kinetics; buněčné linie; mitogenem aktivovaná proteinkinasa 8; Cytokines; ras Proteins; Anthracenes; Mitochondria; makrofágy; Apoptosis; ras proteiny; Mitogen-Activated Protein Kinase 8; STAT3 Transcription Factor; T-2 Toxin; T-2 toxin; cytokiny; Models, Biological; fluorescenční protilátková technika; Macrophages; Mice; Fluorescent Antibody Technique; Janus kinasy; signální transdukce; myši; Signal Transduction; Cell Line; Janus Kinases; mitochondrie; anthraceny; regulace genové exprese; transkripční faktor STAT3; fosforylace; ribozomy; Cell Survival; Gene Expression Regulation; zvířata; viabilita buněk; kinetika; Phosphorylation